(untitled) (Journal of the College of Education for Women, 2019)
AbstractDame Ngaio Edith Marsh (1899-1982), a writer of detective fiction, was bornat Christchurch, New Zealand. Her hero, Chief Detective Inspector Roderick Alleyn,appears in her first novel, A Man Lay Dead (1934), and in subsequent novelsincluding Death and the Dancing Footman (1942). She wrote twenty detective novels.The Dancing Footman, Thomas, listening to a playful song from the smokingroom’sradio where William lay dead after being killed by his brother, Nicholas,provides the most suspected guest at Highfold with badly needed alibi. The murderer,Nicholas, plans an almost perfect crime, but the dance of this footman spoils hisscheme. When Alleyn and his group of policemen stage a show in which there is areconstruction of the murder, Nicholas collapses, and tries to escape, hits Bailey,Alleyn’s finger-print specialist, but they overpower him and take him away with thetwo corpses of his mother and brother.